Analisis Evaluasi Tata Kelola dan Kemanfaatan Program Kampung di Kampung Nayaro Distrik Mimika Baru Kabupaten Mimika - Ida Ayu Purba Riani; Yundy Hafizrianda (Jurnal Kajian Ekonomi dan Studi Pembangunan, 2023)
This research aims to identify leading sectors and changes in the economic structure without mining in Mimika This research aims: (1) to assess the governance of the village program implemented by the Nayaro Village POKJA (teamwork); and (2) to assess the benefits of the program that have been obtained by the community, especially the Kamoro tribe, so far. The approach used in this research is quantitative-descriptive, using a set of evaluation instruments to assess the governance and benefits of the Village Program, where the assessment is carried out using the Guttman Scale. The results of this research show that: (1) The governance of the village program implemented by the POKJA Nayaro Team is still considered poor because it is not transparent and accountable. This is mainly indicated by the failure to prepare Minutes of Agreement based on proposals from village deliberations, not publicizing the implementation of programs and activities to beneficiaries, not explaining the process and mechanism for complaints to beneficiaries, as well as the preparation of accountability reports that do not meet minimum standards; (2) Even though it is considered that the program management is still not good, in terms of the benefits of the program, the Kamoro community considers that the Village Program is very useful. However, please note that in the next stage, the focus should be more on efforts to empower the village economy and the economy of the Kamoro community. Keywords : Program Governance, Program Benefits, Guttman Scale